2019
DOI: 10.1111/birt.12433
|View full text |Cite
|
Sign up to set email alerts
|

Strong Start in birth centers: Socio‐demographic characteristics, care processes, and outcomes for mothers and newborns

Abstract: Background A recent Center for Medicare and Medicaid Innovation report evaluated the four‐year Strong Start for Mothers and Newborns Initiative, which sought to improve maternal and newborn outcomes through exploration of three enhanced, evidence‐based care models. This paper reports the socio‐demographic characteristics, care processes, and outcomes for mothers and newborns engaged in care with American Association of Birth Centers (AABC) sites. Methods The authors examined data for 6424 Medicaid or Children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 27 publications
(39 reference statements)
3
71
0
1
Order By: Relevance
“…6 Risk factors such as depression, history of intimate partner violence, and food insecurity were present in the birth center care sample at levels similar to or higher than national averages. 6,9,11 Participants were at higher risk of experiencing preterm and low birth weight births due to psychosocial risk factors than in previous national birth center studies. 6,9…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…6 Risk factors such as depression, history of intimate partner violence, and food insecurity were present in the birth center care sample at levels similar to or higher than national averages. 6,9,11 Participants were at higher risk of experiencing preterm and low birth weight births due to psychosocial risk factors than in previous national birth center studies. 6,9…”
Section: Introductionmentioning
confidence: 83%
“…6,9,11 Participants were at higher risk of experiencing preterm and low birth weight births due to psychosocial risk factors than in previous national birth center studies. 6,9…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…A qualitative analysis of interviews of 10 projects in England using peer support during pregnancy highlights disadvantaged women's unwillingness to open up to professionals, but these women felt socially connected, valued, and empowered through the peer support process . That said, data from the Centers for Medicare and Medicaid Strong Start Initiative showed that the midwifery care model delivered through birth centers to women with similar social and behavioral risks as a national sample resulted in a remarkably lower PTB rate (4.42%) and LBW rate (3.28%) . Although there were racial and ethnic disparities in the results, they were much less than the national disparities.…”
Section: Featured Reviewsmentioning
confidence: 99%